Focal Mechanism of Volcano-tectonic Earthquakes at Merapi Volcano, Indonesia - Sri Hidayati; Antonius Ratdomopurbo; Kazuhiro Ishihara; Masato Iguchi (Indonesian Journal of Physics, 2008)
Merapi (2968 m), located in central Java, is one of the most active and dangerous volcanoes in Indonesia. The volcano has repeated episodes of dome growth and collapse, producing pyroclastic flows during historical time. Volcano-tectonic (VT) earthquakes have been classified into deep (VTA) and shallow one (VTB). Since August 2000, number of VT events (M=1.0-1.6) had increased, and pyroclastic flows have successively occurred from the middle of January, 2001. The focal zone vertically extends to about 4 km deep beneath the summit. VTA events are located at the depth 2.2-4.1 km and the VTB ones at the depth shallower than 1.3 km. An aseismic zone is observed around 1.3-2.2 km deep between the hypocenter zones of the two types of VT earthquakes, interpreted as shallow magma storage. Focal mechanism of VT events was estimated by using both polarity and amplitude of P-wave first motions at 4 seismic stations, assuming double couple mechanism and homogenous medium. Determined focal mechanisms for VTA events are of normal-fault types. VTA events might originate by increase in horizontal tension when magma rose up from deeper portion. Orientation of their T-axes is nearly horizontal in NEE-SWW direction which might be affected by the E-W regional tectonic stress. As for the VTB, normal fault types dominate the deep VTB zone, while at the shallow part, both reverse fault and normal fault types are originated. The pressure increases at shallow magma storage may cause generation of deep VTB events of normal fault types. As VTB events frequently originated, corresponding to increase of multiphase (MP) events which are related to growth of lava dome, shallow VTB events of reverse fault type might be generated by horizontal compression related to pressure decrease in magma conduit due to extrusion of lava and gases, and occasionally by pressure increase at the shallow part due to accumulation of magma or volcanic gases.